1990
DOI: 10.21273/hortsci.25.8.863f
|View full text |Cite
|
Sign up to set email alerts
|

Critical Tissue Moisture Levels Needed for Maintenance of Rose Plant Viability.

Abstract: Field grown `Mr. Lincoln' rose plants were dug and wrapped in plastic to reduce moisture loss during transport to the lab. Plants were then pruned, weighed, and returned to the plastic cover. After recording initial weights, plants were allowed to dry for 0, 1, 4, 7, or 24 hours at 16°C. Plants were then oven dried, potted, or soaked in water for 20 hours before potting for each drying time treatment. The potted plants were forced to first flower in a glasshouse at which time growth measurements were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Increasing drying time linearly reduced performance rating from 3.2 to 2.0 when data were pooled over all cultivars. Previous studies reported delayed onset of flowering, fewer flowers, and overall poorer performance of roses exposed to desiccating conditions before field planting (Pemberton and Roberson, 1990;Schuch et al, 1995;Welch and Cameron, 1990). This study shows that moisture loss resulting in plant moisture content below 43% has a negative effect on rose plants forced in containers as well.…”
Section: Resultssupporting
confidence: 49%
See 3 more Smart Citations
“…Increasing drying time linearly reduced performance rating from 3.2 to 2.0 when data were pooled over all cultivars. Previous studies reported delayed onset of flowering, fewer flowers, and overall poorer performance of roses exposed to desiccating conditions before field planting (Pemberton and Roberson, 1990;Schuch et al, 1995;Welch and Cameron, 1990). This study shows that moisture loss resulting in plant moisture content below 43% has a negative effect on rose plants forced in containers as well.…”
Section: Resultssupporting
confidence: 49%
“…3). A previous study of containerized roses found that moisture content between 33% and 41% was critical for survival (Pemberton and Roberson, 1990). Also, packaged plants with moisture content between 28% and 43% resulted in reduced new growth and greater mortality for some cultivars after field planting when compared with packaged rose plants with plant moisture of 50% (Welch and Cameron, 1990).…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations